2018
DOI: 10.1055/s-0043-123763
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Target Genes in Pituitary Adenomas

Abstract: Pituitary adenomas account for the top three primary intracranial tumors in terms of total incidence rates. The clinical symptoms presented by the disease are often characterized by a series of systemic endocrine disorders, severe occupational lesions, and even some malignant features, and therefore early diagnosis and predicting recurrence would be instructive for clinical treatment of pituitary adenomas. An increasing number of specific microRNA (miRNA) expression signatures have been identified in pituitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 76 publications
(77 reference statements)
0
31
0
Order By: Relevance
“…Overexpression of miR-16 inhibits the proliferation of PA cells HP75 and promotes apoptosis by targeting HMGA2 expression [23]. However, the comprehensive and specific effects of miRNAs in PA invasion behavior are still rarely reported [24]. Thus, we recognized 55DEMs in IPAs by RNA sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-16 inhibits the proliferation of PA cells HP75 and promotes apoptosis by targeting HMGA2 expression [23]. However, the comprehensive and specific effects of miRNAs in PA invasion behavior are still rarely reported [24]. Thus, we recognized 55DEMs in IPAs by RNA sequencing analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Their long list illustrates the heterogeneity of factors that can contribute to the formation of a tumor. While this complicates the choice of miRNAs to use for diagnostic purposes, miR-10b, miR-16, miR-26a, miR-503 and miR-514 have been found upregulated or downregulated in at least four different pituitary tumor subtypes and therefore could be superior markers for tumor screening [89]. On top of this, other studies found miR196a-2 and miR-212 to be deregulated in all pituitary tumor types.…”
Section: Micro-rnasmentioning
confidence: 99%
“…Exosomes, in addition to transferring miRNAs, are used to transfer other information, such as DNA, mRNA, proteins, etc., from one cell to another, and tumor cells play a particularly important role in exosome production [ 7 ]. Progression from benign PAs to its aggressive forms is accompanied by cumulative changes at the molecular level, where miRNAs play a direct role [ 8 ]. Dysregulation of miRNAs in tumor cells is a hallmark of a tumor, and miRNAs can play a role as tumor suppressors or oncogenes depending on the cellular context and various functions of the target genes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%